2019
DOI: 10.1186/s12964-019-0321-y
|View full text |Cite
|
Sign up to set email alerts
|

Gut ghrelin regulates hepatic glucose production and insulin signaling via a gut-brain-liver pathway

Abstract: BackgroundGhrelin modulates many physiological processes. However, the effects of intestinal ghrelin on hepatic glucose production (HGP) are still unclear. The current study was to explore the roles of intestinal ghrelin on glucose homeostasis and insulin signaling in the liver.MethodsThe system of intraduodenal infusion and intracerebral microinfusion into the nucleus of the solitary tract (NTS) in the normal chow-diet rats and pancreatic-euglycemic clamp procedure (PEC) combined with [3-3H] glucose as a trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…The phosphorylation of IRS1 at Ser307 site has been shown to impair insulin signaling (12,13), which was reported as one of the major postreceptor factors involved in IR in skin fibroblasts and skeletal muscle cells from patients with PCOS (3,9,32). The phosphorylation of IR-b Tyr1150/115, the phosphorylation of IRS1/2 Tyr612, and the phosphorylation of Akt Ser473 were important insulin signaling molecules (33)(34)(35)(36)(37). Here, we found that the insulin-induced Ser307 19).…”
Section: Discussionmentioning
confidence: 59%
“…The phosphorylation of IRS1 at Ser307 site has been shown to impair insulin signaling (12,13), which was reported as one of the major postreceptor factors involved in IR in skin fibroblasts and skeletal muscle cells from patients with PCOS (3,9,32). The phosphorylation of IR-b Tyr1150/115, the phosphorylation of IRS1/2 Tyr612, and the phosphorylation of Akt Ser473 were important insulin signaling molecules (33)(34)(35)(36)(37). Here, we found that the insulin-induced Ser307 19).…”
Section: Discussionmentioning
confidence: 59%
“…2012). Perhaps the most well-known of the gut-derived hormones released during fasting is ghrelin, with intraduodenal infusion increasing hepatic glucose production via GSH-R1a receptors on vagal afferents signalling to the NTS (Lin et al . 2019).…”
Section: Gut Hormone Regulation Of Metabolismmentioning
confidence: 99%
“…It has been reported that gut infusion of ghrelin inhibited increased hepatic glucose production and expression of gluconeogenic enzymes and decreased insulin signaling in the rat liver. Co-infusion with the NMDAR inhibitor negated gut ghrelin effects within the dorsal vagal complex 53 . However, further studies are required to assess whether NMDA-induced insulin resistance is dependent on the activation of NMDAR in the liver.…”
Section: Discussionmentioning
confidence: 96%